Synthesis of hydrogen storage materials in a Ti-Zr-Ni system using the hydride cycle technology during dehydrogenation by an electron beam in a vacuum - Dmytrenko, O.E.; Dubinko, V.I.; Borysenko, V.M.; Irwin, K. (Вопросы атомной науки и техники, 2020)
The synthesis of intermetallic material was carried out by means of dehydrogenating annealing of a (TiH₂)₃₀Zr₄₅Ni₂₅ sample in vacuum by an electron beam. The properties of the obtained material were studied for establishing the structural phase composition by scanning electron microscopy and X-ray structural analysis. It was found that prolonged exposure of an electron beam to a sample containing titanium hydride leads to a number of structural transformations in the material, accompanied by a redistribution of hydrogen from titanium to zirconium and culminating in the synthesis of a ternary alloy with characteristic growth structures. The processes of hydrogen sorption-desorption by a synthesized sample were studied, the temperature ranges of these processes and the absorption capacity of the obtained material were established. It was shown that the structure of the sample formed upon heating by an electron beam promotes the absorption of hydrogen at room temperature up to 1.41 wt.%.